2022
DOI: 10.1155/2022/5446751
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation by Phone Counselling in a Lung Cancer Screening Program: A Retrospective Comparative Cohort Study

Abstract: Introduction. Smoking cessation integration within lung cancer screening programs is challenging. Currently, phone counselling is available across Canada for individuals referred by healthcare workers and by self-referral. We compared quit rates after phone counselling interventions between participants who self-refer, those referred by healthcare workers, and those referred by a lung cancer screening program. Methods. This is a retrospective cohort study of participants referred to provincial smoking cessatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Le terapie cognitive e comportamentali vengono condotte in ogni fase del follow-up, aumentano l'efficacia delle medicazioni, rafforzano il senso di autoefficacia del paziente, la compliance terapeutica e consentono un migliore controllo del desiderio (craving) [3,5,[25][26][27]. Il supporto a distanza (consulenza telefonica) rafforza l'astinenza dei pazienti, così come la casa senza fumo [3,5,25,26,28,29].…”
Section: Terapie Cognitive E Comportamentali (Cbt)unclassified
See 1 more Smart Citation
“…Le terapie cognitive e comportamentali vengono condotte in ogni fase del follow-up, aumentano l'efficacia delle medicazioni, rafforzano il senso di autoefficacia del paziente, la compliance terapeutica e consentono un migliore controllo del desiderio (craving) [3,5,[25][26][27]. Il supporto a distanza (consulenza telefonica) rafforza l'astinenza dei pazienti, così come la casa senza fumo [3,5,25,26,28,29].…”
Section: Terapie Cognitive E Comportamentali (Cbt)unclassified
“…Cognitive and behavioral therapies (CBT)Cognitive and behavioral therapies (CBT) are conducted at each step of follow-up, increase the efficacy of médications, reinforce the patient's sense of self-efficacy, therapeutic compliance, enable better control of craving[3,5,[25][26][27]. Long-distance support (telephone counselling) reinforce patients abstinence, as well as smokefree home[3,5,25,26,28,29].…”
mentioning
confidence: 99%
“…Taylor et al demonstrated phone counseling and NRT provided with LCS is an effective strategy to increase short-term quit rates [27]. However, a separate study evaluating quit rates by telephone counseling of participants referred from an LCS program found low quit rates compared with self-referred patients, suggesting a multimodal or personalized approach should be considered [28]. Moreover, NLST findings also were notable for the lowest quit rate in patients with a low risk or ‘normal scan’, suggesting wrong lesson could be taken away from the teachable moment of LCS [25].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…3,5,22 Long-distance support (telephone counselling) help patients to maintain abstinence and a smoke-free home. 5,22,23 The combination of short-acting nicotine replacement therapy (NRT) (gum, lozenge, spray) and long-acting NRT (patch) with a duration of 12 to 24 weeks, increases the odds of success nearly 3-fold compared with placebo (OR= 2.73; CI 95%: 2.07-3.65). No carcinogenic effects of NRT have been reported.…”
Section: Smoking Cessation Enhances Chemotherapy Efficacymentioning
confidence: 99%